2015
DOI: 10.1007/s11743-015-1766-7
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Surface Activities of Modified Soy Protein–Dextrin Surfactants

Abstract: A series of polymeric surfactants has been prepared through the reaction of soy protein with polyethoxylated stearyl ethers of various hydrophilic chain lengths. These surfactants exhibited surface activity, evaluated using surface tension, foaming, and wetting power that was superior to that of traditional surfactants containing only one hydrophobic moiety and one hydrophilic head group. Changing the ethoxylate (EO) group length had a significant effect on the surface activity. Increasing the EO group length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The treatment caused disruption of protein hydrogen bonds and hydrophobic interactions, and formed polypeptides with more flexible structure. A decrease in CMC values suggested an enhancement in the interfacial properties of the peptides ( Lin, Lai, Chen, & Li, 2016 ). The flexible structure of WGHs led to a notable increase in contact area and promoted hydrophobic interactions between naringin and hydrolysates.…”
Section: Resultsmentioning
confidence: 99%
“…The treatment caused disruption of protein hydrogen bonds and hydrophobic interactions, and formed polypeptides with more flexible structure. A decrease in CMC values suggested an enhancement in the interfacial properties of the peptides ( Lin, Lai, Chen, & Li, 2016 ). The flexible structure of WGHs led to a notable increase in contact area and promoted hydrophobic interactions between naringin and hydrolysates.…”
Section: Resultsmentioning
confidence: 99%
“…These results revealed that the polyol solvents in this experiment effectively extracted the quintessential ingredients of C. oleifera Abel dregs. The extracts in this study exhibited strong UVA and UVB absorbance, rendering them ideal for application in sunscreens [17, 18, 19, 20].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the wetting ability of surfactants may accelerate the diffusion or penetration of dyestuffs into fibrous materials and improve their effectiveness and efficiency during the process of dyeing leather or textiles. In general, the wetting ability of a surfactant can be characterized by the contact angle (θ) of its droplet on the surface of a substrate: the smaller the contact angle, the better its wetting ability (Lin, Lai, Chen, & Li, 2016). In this study, we used a paraffin sheet, a chrome-tanned leather, and a cotton fabric to assess the wettability of CBES.…”
Section: Application Propertiesmentioning
confidence: 99%